MEKANISME PASAR PADA SEKTOR KESEHATAN - Dianah Afra Faadhilah; Ummi Saidah Ramhan; Imelda Yanti Aidil Fitriana; Virnaz Permata Ayu; Rendi Alparizi; Syafrudin; Latifatul Husna; Ayu Marlina; Lale Ajeng Khalifatun Wardani (Nusadaya Journal of Multidiciplinary Studies, 2022)
The market mechanism assumes that in behaving, everyone basically has personal desires and always seeks maximum satisfaction. Whereas equity reflects behavior that is less selfish and pays attention to the welfare of others. Health and illness also affect a person's ability to earn income. Government intervention on health services can be based on the principles of efficiency and equity. This can be attempted by improving the conditions needed for the market mechanism to function or limiting the effects that cause the market to not function.